MOTIVATIONAL READINESS OF STUDENTS TO WORK WITH CONVICTED PRISONERS IN UKRAINE - Klishevich, Nataliia; Sulitskyi, Vadym (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The ongoing reform of Ukrainian penitentiary service places high demands on the moral and psychological qualities of correctional staff facilities. Particular attention is paid to the issues of motivation and motivational readiness of employees in difficult, special conditions with clients of the correctional system. Therefore, the aim of our study was to establish and analyze how much motivational readiness has been formed among cadets and students to work with prisoners in prison, to identify whether there are patterns that affect the formation of positive or negative motivation in the process of professional training. In our work, we used the following methods: analysis of statistical data of personnel of the State Penitentiary Service of Ukraine, which are in the public domain; questionnaires; interview.  We identified four main motives that positively affect the choice of work in a correctional facility: social security; fight against crime; retirement; work with people. At the same time, there are factors that form a negative motivation for employees, namely: working and resting conditions; lack of visible work results; negative impact of the criminal environment and subculture, which contribute to psycho-emotional burnout and professional deformation of the staff of correctional facilities. The results allow revising the curriculum for training of personnel for working with clients of the correctional system; reveals the existing problems of employees of the State Penitentiary Service of Ukraine; have a positive impact on reducing the number of layoffs among staff; helps to draw attention to professional, moral and ethical qualities when accepting candidates for work in correctional facilities.